The ontology as the privileged horizon of Plato’s thought - Bocayuva, Izabela (Revista Archai, 2010)
The education is, no doubt, a fundamental question in Plato’s thought. The Republic, considerate by many people as his masterpiece, takes care of this aspect, not without directing it through a political obliquity. In the greek society that honoured, above all, the formation of free citizens, education and politics were necessarily together. Nevertheless, we want to punctuate how, to Plato, both of them are subordinate to the ontological question.